Preparation method of magnesium alloy surface high-friction-resistant composite film
Patent Information
- Application Number
- CN202410677878.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-29
AI Technical Summary
然而,镁合金化学性质活泼,在空气中易被氧化耐腐蚀性能差,同时由于镁合金硬度较低,在实际使用中容易造成擦伤和磨损,在一定程度上限制了镁合金在工业上的发展和应用,而表面处理是一种改善其耐蚀性和耐摩擦性的有效方法
[0019] 1. This invention provides a method for preparing a high friction-resistant composite film on a magnesium alloy surface. A friction-resistant composite layer is established on the magnesium alloy surface through a composite oxidation/sol modification method. The Vickers hardness of the composite film layer reaches 732HV, the surface friction coefficient is between 0.10 and 0.16, and it also has good corrosion resistance.
Smart Images

Figure BDA0004864739320000041 
Figure BDA0004864739320000071
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface modification technology of metal materials, and specifically relates to a method for preparing a high friction-resistant composite film on the surface of magnesium alloy. Background Technology
[0002] Magnesium alloys are the lightest metallic engineering materials in the world, with most magnesium alloys typically having a density between 1.75 and 1.90 g / cm³. 3 Magnesium alloys have a density approximately 80% lower than steel, 60% lower than titanium, and 40% lower than aluminum alloys. Besides their low density, magnesium alloys possess many other excellent properties, such as good plasticity and low-temperature toughness, high specific strength and specific modulus, good damping and shock absorption, excellent thermal conductivity, minimal anisotropy, and a stronger ability to withstand impact loads than other alloys, earning them the reputation of "green engineering materials of the 21st century." In recent years, magnesium alloys have been widely used in aerospace, transportation, electronics, chemical, and metallurgical industries. However, magnesium alloys are chemically reactive, easily oxidized in air, and have poor corrosion resistance. Furthermore, their relatively low hardness makes them prone to scratches and wear in practical use, which to some extent limits their industrial development and application. Surface treatment is an effective method to improve their corrosion resistance and abrasion resistance.
[0003] Currently, there is considerable research on surface treatments to improve the corrosion resistance of magnesium alloys, but limited research on surface treatments to improve wear resistance. The main methods include electroplating and electrodeposition to deposit metal layers on the metal surface, which are complex, costly, and environmentally unfriendly; or inorganic / organic coatings, which are simple to apply but prone to peeling and flaking. Therefore, to improve the multi-application scenarios of magnesium alloys, reduce wear during dynamic processes, and extend their service life, developing a high-friction-resistant composite film for magnesium alloy surfaces is of great significance. Summary of the Invention
[0004] In view of the limitations and deficiencies of the prior art, the present invention provides a method for preparing a high friction-resistant composite film on the surface of magnesium alloy, aiming to improve the friction resistance of magnesium alloy materials while achieving good corrosion resistance.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A method for preparing a high-friction-resistant composite film on a magnesium alloy surface includes the following steps:
[0007] S1. Polish the magnesium alloy surface until it is shiny, and clean it with acetone until the surface is clean.
[0008] S2. Place the polished and cleaned magnesium alloy in a composite oxide solution and stir at a temperature of 25-45℃ for 5-20 minutes at a stirring rate of 50-100 r / min to obtain a magnesium alloy with an oxide film layer.
[0009] S3. Add tetraethyl orthosilicate, boric acid, and deionized water to anhydrous ethanol. Stir at 700-850 r / min for 0.5-1.5 h at room temperature (25℃). Then, add 0.1 mol / L hydrochloric acid dropwise to adjust the pH of the solution to 2-3. Continue stirring for 6-8 h to obtain boron-doped silica sol. Next, immerse the magnesium alloy with the oxide film in the sol for 2-3 h. After removal, dry it in a 60℃ forced-air drying oven for 10-12 h. Finally, calcine it in an air atmosphere in a muffle furnace at 200-300℃ for 40-60 min with a heating rate of 0.5-1℃ / min to form a highly abrasion-resistant composite film on the surface of the magnesium alloy.
[0010] Further, the preparation method of the composite oxidation liquid is as follows: add an organosilane film-forming agent to deionized water, stir at 500-800 r / min for 3-4 h at 20-30℃, then raise the temperature to 55-65℃, and add ionic liquid, molybdate, tungstate, complexing agent, paeonol and sodium alginate in sequence, and continue stirring at constant temperature for 5-8 h to obtain the composite oxidation liquid base solution; according to the mass ratio of composite oxidation liquid base solution to deionized water of 5%-20%: 95%-80%, add deionized water to the composite oxidation liquid base solution for dilution to obtain the composite oxidation liquid.
[0011] Furthermore, in preparing the composite oxidizing liquid base, the solid-liquid ratio of the organosilane film-forming agent, ionic liquid, molybdate, tungstate, complexing agent, paeonol, sodium alginate, and deionized water is 30-50g:20-30mL:15-30g:10-20g:4-6g:3-5g:5-10g:0.5L.
[0012] Furthermore, the organosilane film-forming agent is any one of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-epoxypropyltrimethoxysilane.
[0013] Furthermore, the ionic liquid is any one or any two of the pyrazole-based ionic liquids 1-butyl-2-hexylpyrazole bis(trifluoromethanesulfonyl)amide, 1-butyl-2-octylpyrazole bis(trifluoromethanesulfonyl)amide, and 1-butyl-2-decylpyrazole bis(trifluoromethanesulfonyl)amide mixed in a mass ratio of 1:1. The method for preparing the ionic liquid includes the following steps: adding 1-butyl-2-hexylpyrazole bromide or 1-butyl-2-octylpyrazole bromide or 1-butyl-2-decylpyrazole bromide and lithium bis(trifluoromethanesulfonyl)imide to deionized water, stirring at 400-600 r / min for 3-4 h at 30-50 °C to obtain 1-butyl-2-hexylpyrazole bis(trifluoromethanesulfonyl)amide, 1-butyl-2-octylpyrazole bis(trifluoromethanesulfonyl)amide, and 1-butyl-2-decylpyrazole bis(trifluoromethanesulfonyl)amide, wherein the molar ratio of deionized water, 1-butyl-2-hexylpyrazole bromide or 1-butyl-2-octylpyrazole bromide or 1-butyl-2-decylpyrazole bromide, and lithium bis(trifluoromethanesulfonyl)imide is 100-120:1:1.2.
[0014] Furthermore, the molybdate is any one or any two of sodium molybdate, potassium molybdate, and calcium molybdate mixed in a mass ratio of 1:1, or is a mixture of sodium molybdate, potassium molybdate, and calcium molybdate in a mass ratio of 1:1:1.
[0015] Furthermore, the tungstate is any one or any two of sodium tungstate, potassium tungstate, and ammonium tungstate mixed in a mass ratio of 1:1.
[0016] Furthermore, the complexing agent is any one of disodium ethylenediaminetetraacetate and sodium aminotriacetate, or a mixture thereof in a mass ratio of 1:1.
[0017] Furthermore, in preparing the boron-doped silica sol, the volume ratio of anhydrous ethanol, tetraethyl orthosilicate, boric acid, and deionized water is 8-12:13:1-3:4-6.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] 1. This invention provides a method for preparing a high friction-resistant composite film on a magnesium alloy surface. A friction-resistant composite layer is established on the magnesium alloy surface through a composite oxidation / sol modification method. The Vickers hardness of the composite film layer reaches 732HV, the surface friction coefficient is between 0.10 and 0.16, and it also has good corrosion resistance.
[0020] 2. This invention improves the corrosion resistance of the composite film through multiple effects of organosilane film formation, ionic liquid, inorganic-organic composite corrosion inhibitor, and natural corrosion inhibitor.
[0021] 3. Modifying the composite oxide film by boron-doped silica sol can improve the hardness of the composite film while reducing the coefficient of friction; calcination temperature in the range of 200-300℃ can simultaneously meet the goals of excellent adhesion of the composite coating and protection of the magnesium alloy body; heating rate in the range of 0.5-1℃ / min is beneficial to improve the density of the coating, while also improving the hardness and wear resistance of the coating. Detailed Implementation
[0022] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1
[0024] The preparation method of the composite oxidation liquid includes the following steps:
[0025] Add 40g of γ-aminopropyltrimethoxysilane to 0.5L of deionized water, stir at 600r / min for 3h at 25℃, then raise the temperature to 60℃ and add 26mL of ionic liquid (13mL of 1-butyl-2-hexylpyrazole bis(trifluoromethanesulfonyl)amide and 13mL of 1-butyl-2-octylpyrazole bis(trifluoromethanesulfonyl)amide), 24g of molybdate (8g of potassium molybdate, 8g of sodium molybdate and 8g of calcium molybdate), 16g of tungstate (8g of sodium tungstate and 8g of ammonium tungstate), 5g of complexing agent (disodium ethylenediaminetetraacetate), 4g of paeonol and 8g of sodium alginate, and continue stirring at constant temperature for 5-8h to obtain the composite oxidizing liquid base.
[0026] The composite oxidation solution is diluted with deionized water by adding deionized water at a mass ratio of 15% to 85% to obtain a composite oxidation solution with a mass concentration of 15%.
[0027] Examples 2-5
[0028] The preparation method of the composite oxidation liquid is the same as that in Example 1, except that the proportions of each component in the base liquid are different, as shown in Table 1.
[0029] Comparative Example 1
[0030] The preparation method of the composite oxidation liquid is the control group of Example 1, except that the organosilane is replaced with polyvinylpyrrolidone, while the other components and preparation steps remain unchanged.
[0031] Comparative Example 2
[0032] The preparation method of the composite oxidation liquid is the control group of Example 1, except that no ionic liquid is added, while the other components and preparation steps remain unchanged.
[0033] Comparative Example 3
[0034] The preparation method of the composite oxidation liquid is the control group of Example 1, except that paeonol is not added, while the other components and preparation steps remain unchanged.
[0035] Table 1. Formulation of composite oxidation liquid base solution
[0036]
[0037] Example 6
[0038] A method for preparing a high-friction-resistant composite film on a magnesium alloy surface includes the following steps:
[0039] S1. Magnesium alloy surface pretreatment: Grind the magnesium alloy until it is bright and clean it with acetone until the surface is clean.
[0040] S2. Composite oxidation treatment: The polished and cleaned magnesium alloy was placed in a composite oxidation solution with a mass fraction of 15% prepared in Example 1, and stirred at 40°C for 1 hour at a stirring rate of 100 r / min to obtain a magnesium alloy with an oxide film layer.
[0041] S3. Boron-doped silica sol modification: Tetraethyl orthosilicate, boric acid, and deionized water were added to anhydrous ethanol and stirred at 800 r / min for 1 h at room temperature (25℃). Then, 0.1 mol / L hydrochloric acid was added dropwise to adjust the pH of the solution to 2, and stirring was continued for 8 h to obtain boron-doped silica sol. The volume ratio of anhydrous ethanol, tetraethyl orthosilicate, boric acid, and deionized water was 10:13:2:5. Next, a magnesium alloy with an oxide film was immersed in the sol for 2 h, removed, and dried in a 60℃ forced-air drying oven for 10 h. Finally, it was calcined in a muffle furnace at 200℃ for 60 min under air atmosphere, with a heating rate of 0.5℃ / min.
[0042] Example 7
[0043] A method for preparing a high-friction-resistant composite film on a magnesium alloy surface includes the following steps:
[0044] S1. Magnesium alloy surface pretreatment: Grind the magnesium alloy until it is bright and clean it with acetone until the surface is clean.
[0045] S2. Composite oxidation treatment: The polished and cleaned magnesium alloy was placed in a composite oxidation solution with a mass fraction of 15% prepared in Example 1, and stirred at 40°C for 1 hour at a stirring rate of 100 r / min to obtain a magnesium alloy with an oxide film layer.
[0046] S3. Boron-doped silica sol modification: Tetraethyl orthosilicate, boric acid, and deionized water were added to anhydrous ethanol and stirred at 800 r / min for 1 h at room temperature (25℃). Then, 0.1 mol / L hydrochloric acid was added dropwise to adjust the pH of the solution to 3, and stirring was continued for 8 h to obtain boron-doped silica sol. The volume ratio of anhydrous ethanol, tetraethyl orthosilicate, boric acid, and deionized water was 10:13:2:5. Magnesium alloys with oxide films were then immersed in the sol for 2 h, removed, and dried in a 60℃ forced-air drying oven for 10 h. Finally, they were calcined in a muffle furnace at 300℃ for 40 min under air atmosphere, with a heating rate of 1℃ / min.
[0047] Example 8
[0048] A method for preparing a high-friction-resistant composite film on a magnesium alloy surface includes the following steps:
[0049] S1. Magnesium alloy surface pretreatment: Grind the magnesium alloy until it is bright and clean it with acetone until the surface is clean.
[0050] S2. Composite oxidation treatment: The polished and cleaned magnesium alloy was placed in a composite oxidation solution with a mass fraction of 15% prepared in Example 1, and stirred at 40°C for 1 hour at a stirring rate of 100 r / min to obtain a magnesium alloy with an oxide film layer.
[0051] S3. Boron-doped silica sol modification: Tetraethyl orthosilicate, boric acid, and deionized water were added to anhydrous ethanol and stirred at 800 r / min for 1 h at room temperature (25℃). Then, 0.1 mol / L hydrochloric acid was added dropwise to adjust the pH of the solution to 2.5, and stirring was continued for 8 h to obtain boron-doped silica sol. The volume ratio of anhydrous ethanol, tetraethyl orthosilicate, boric acid, and deionized water was 10:13:2:5. Magnesium alloy with an oxide film was then immersed in the sol for 2 h, removed, and dried in a 60℃ forced-air drying oven for 10 h. Finally, it was calcined in a muffle furnace at 250℃ for 50 min under air atmosphere, with a heating rate of 0.5℃ / min.
[0052] Example 9
[0053] A method for preparing a high friction-resistant composite film on a magnesium alloy surface, the specific preparation process and parameter settings are the same as in Example 6, the difference being that step S2 uses the composite oxide liquid prepared in Example 2.
[0054] Example 10
[0055] A method for preparing a high friction-resistant composite film on a magnesium alloy surface, the specific preparation process and parameter settings are the same as in Example 6, the difference being that step S2 uses the composite oxide liquid prepared in Example 3.
[0056] Example 11
[0057] A method for preparing a high friction-resistant composite film on a magnesium alloy surface, the specific preparation process and parameter settings are the same as in Example 6, the difference being that step S2 uses the composite oxide liquid prepared in Example 4.
[0058] Example 12
[0059] A method for preparing a high friction-resistant composite film on a magnesium alloy surface, the specific preparation process and parameter settings are the same as in Example 6, the difference being that step S2 uses the composite oxide liquid prepared in Example 5.
[0060] Comparative Example 4
[0061] A method for preparing a high friction-resistant composite film on a magnesium alloy surface is used as the control group of Example 6. The difference is that step S2 uses the composite oxide liquid prepared in Comparative Example 1, while the other components and preparation steps remain unchanged.
[0062] Comparative Example 5
[0063] A method for preparing a high friction-resistant composite film on a magnesium alloy surface is used as the control group of Example 6. The difference is that step S2 uses the composite oxide liquid prepared in Comparative Example 2, while the other components and preparation steps remain unchanged.
[0064] Comparative Example 6
[0065] A method for preparing a high friction-resistant composite film on a magnesium alloy surface is used as the control group of Example 6. The difference is that step S2 uses the composite oxide liquid prepared in Comparative Example 3, while the other components and preparation steps remain unchanged.
[0066] Comparative Example 7
[0067] A method for preparing a high-friction-resistant composite film on a magnesium alloy surface is used as the control group of Example 6, except that the calcination temperature in the muffle furnace in step S3 is 150°C, while the other components and preparation steps remain unchanged.
[0068] Comparative Example 8
[0069] A method for preparing a high friction-resistant composite film on a magnesium alloy surface is used as the control group of Example 6, except that the calcination temperature in the muffle furnace in step S3 is 400℃, while the other components and preparation steps remain unchanged.
[0070] Comparative Example 9
[0071] A method for preparing a high-friction-resistant composite film on a magnesium alloy surface is used as the control group of Example 6. The difference is that the heating rate of the muffle furnace in step S3 is 0.4℃ / min, while the other components and preparation steps remain unchanged.
[0072] Comparative Example 10
[0073] A preparation method of a high friction resistance composite film on a magnesium alloy surface, which is the control group of Example 6, with the difference that the heating rate of the muffle furnace in step S3 is 2°C / min, and other components and preparation steps remain unchanged.
[0074] Comparative Example 11
[0075] A preparation method of a composite film on a magnesium alloy surface, comprising the following steps:
[0076] S1. Pretreatment of magnesium alloy surface: polishing the magnesium alloy until it is bright, and cleaning it with acetone until the surface is clean;
[0077] S2. Composite oxidation treatment: placing the polished and cleaned magnesium alloy in the composite oxidation solution prepared in Example 1 with a mass fraction of 15%, stirring at 40°C for 1 h at a stirring rate of 100 r / min, to obtain a magnesium alloy with an oxide film layer.
[0078] Visual inspection and performance tests are carried out on Examples 6 to 12 and Comparative Examples 4 to 11, and the methods are as follows:
[0079] Visual inspection: the coating is qualified if there is no crack, breakage or discoloration on the appearance, otherwise it is unqualified;
[0080] Corrosion resistance: a neutral salt spray test (GB / T 10125-2021) is carried out on the sample. After 240 h of test, the coating is qualified if there is no corrosion on the surface, otherwise it is unqualified;
[0081] Film hardness: a fully automatic micro Vickers hardness tester is used to measure the Vickers hardness of the film layer;
[0082] Adhesion: a cross-cut test (GB / T 9286-2021) is carried out on the sample, and grading is carried out according to the peeling condition of the coating in the cutting area;
[0083] Friction resistance: according to GB / T 12444-2006, the friction coefficient and wear rate are obtained through ball-on-disk wear test.
[0084] The above inspection and test results are shown in Table 2:
[0085] Table 2
[0086]
[0087] It can be seen from Table 2 that:
[0088] Examples 6, 7, and 8 show the test results of composite films on magnesium alloy surfaces obtained by sol-gel modification under different parameter settings after the same oxidation treatment; Examples 9, 10, 11, and 12 show the test results of composite films obtained by sol-gel modification after oxidizing magnesium alloys with composite oxidizing solutions of different components (prepared from Examples 2, 3, 4, and 5) under the same experimental steps; The results show that the composite films on magnesium alloy surfaces prepared by the surface treatment modification method of the present invention have high hardness, good adhesion, excellent abrasion resistance, and corrosion resistance.
[0089] A comparison of Comparative Examples 4 and 6 shows that the organosilane in the composite oxidation solution is beneficial to improving the corrosion resistance of the magnesium alloy composite film, mainly due to its film-forming effect. A comparison of Comparative Examples 5, 6, and 6 shows that the ionic liquid and paeonol in the composite oxidation solution are beneficial to improving the corrosion resistance of the magnesium alloy composite film. This is because the synergistic effect of the organic corrosion inhibitor, natural corrosion inhibitor, and inorganic corrosion inhibitor can enhance the corrosion resistance of the composite film. Furthermore, a comparison of Comparative Examples 4, 5, 6, and 6 shows that the improved corrosion resistance of the film also helps to better utilize the effect of the sol-gel modification treatment, thereby improving the hardness and abrasion resistance of the composite film.
[0090] Comparing Comparative Examples 7 and 8 with Examples 6, 7, and 8, it can be seen that during the sol-gel modification process, soaking and drying followed by calcination (200-300℃) can solidify the sol, making it more tightly bonded to the oxide layer and thus improving the hardness of the composite film. When the calcination temperature is reduced to below 200℃, the sol layer is not fully solidified, resulting in a decrease in the hardness and bonding strength of the composite film. When the calcination temperature is further increased to 400℃, cracks and fissures appear on the magnesium alloy surface, and the hardness of the composite film decreases. This is because the magnesium alloy has poor high-temperature strength and creep properties, which further reduces its friction resistance.
[0091] As can be seen from the comparison of Comparative Examples 9 and 10 with Examples 6, 7 and 8, the preferred calcination heating rate during the sol-gel modification process is 0.5-1℃ / min, which can obtain a composite film with better abrasion resistance. This is because the nanoparticles generated at a suitable heating rate have smaller particle sizes and are conducive to the gradation of large and small particles, making the composite film more compact. When the heating rate is reduced to 0.4℃ / min or increased to 2℃ / min, the degree of compactness of the composite film structure will decrease, thereby reducing its hardness, bonding strength and abrasion resistance.
[0092] As can be seen from the comparison between Comparative Example 11 and Example 6, the boron-doped silica sol modification treatment improves the corrosion resistance of the film while also increasing the hardness and abrasion resistance of the composite film.
[0093] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0094] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-friction-resistant composite film on a magnesium alloy surface, characterized in that, Includes the following steps: S1. Polish the magnesium alloy surface until it is shiny, and clean it with acetone until the surface is clean; S2. Place the polished and cleaned magnesium alloy in a composite oxide solution and stir it at 25-45℃ for 1 hour at a stirring rate of 50-100 r / min to obtain a magnesium alloy with an oxide film layer. The preparation method of the composite oxidation liquid is as follows: an organosilane film-forming agent is added to deionized water, and the mixture is stirred at 500-800 r / min for 3-4 h at 20-30℃. Then, the temperature is raised to 55-65℃, and ionic liquid, molybdate, tungstate, complexing agent, paeonol, and sodium alginate are added sequentially. The mixture is kept at a constant temperature and stirred for another 5-8 h to obtain the composite oxidation liquid base solution. The composite oxidation liquid base solution to deionized water is diluted with deionized water at a mass ratio of 5%~20%:95%~80% to obtain the composite oxidation liquid. The ionic liquid is any one or any two of the following pyrazole ionic liquids: 1-butyl-2-hexylpyrazole bis(trifluoromethylsulfonyl)amide, 1-butyl-2-octylpyrazole bis(trifluoromethylsulfonyl)amide, and 1-butyl-2-decylpyrazole bis(trifluoromethylsulfonyl)amide, mixed in a mass ratio of 1:
1. S3. Add tetraethyl orthosilicate, boric acid, and deionized water to anhydrous ethanol, and stir at 700-850 r / min for 0.5-1.5 h at room temperature. Then add hydrochloric acid dropwise to adjust the pH of the solution to 2-3, and continue stirring for 6-8 h to obtain boron-doped silica sol. Immerse the magnesium alloy with the oxide film in the sol for 2-3 h, dry it, and then calcine it in a muffle furnace at 200-300℃ for 40-60 min to form a highly abrasion-resistant composite film on the surface of the magnesium alloy.
2. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, When preparing the composite oxidizing liquid base, the solid-liquid ratio of the organosilane film-forming agent, ionic liquid, molybdate, tungstate, complexing agent, paeonol, sodium alginate, and deionized water is 30-50g:20-30mL:15-30g:10-20g:4-6g:3-5g:5-10g:0.5L.
3. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, The organosilane film-forming agent is any one of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-epoxypropyltrimethoxysilane.
4. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, The preparation method of the ionic liquid includes the following steps: adding 1-butyl-2-hexylpyrazole bromide or 1-butyl-2-octylpyrazole bromide or 1-butyl-2-decylpyrazole bromide and lithium bis(trifluoromethanesulfonyl)imide to deionized water, stirring at 30-50℃ and 400-600 r / min for 3-4 h to obtain 1-butyl-2-hexylpyrazole bis(trifluoromethanesulfonyl)amide, 1-butyl-2-octylpyrazole bis(trifluoromethanesulfonyl)amide, and 1-butyl-2-decylpyrazole bis(trifluoromethanesulfonyl)amide, wherein the molar ratio of deionized water, 1-butyl-2-hexylpyrazole bromide or 1-butyl-2-octylpyrazole bromide or 1-butyl-2-decylpyrazole bromide and lithium bis(trifluoromethanesulfonyl)imide is 100-120:1:1.
2.
5. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, The molybdate is formed by mixing any one or any two of sodium molybdate, potassium molybdate, and calcium molybdate in a mass ratio of 1:1, or by mixing sodium molybdate, potassium molybdate, and calcium molybdate in a mass ratio of 1:1:
1.
6. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, The tungstate is formed by mixing any one or any two of sodium tungstate, potassium tungstate, and ammonium tungstate in a mass ratio of 1:
1.
7. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, The complexing agent is any one or any two of disodium ethylenediaminetetraacetate and sodium aminotriacetate mixed in a mass ratio of 1:
1.
8. The method for preparing a high-friction-resistant composite film on a magnesium alloy surface according to claim 1, characterized in that, In preparing the boron-doped silica sol, the volume ratio of anhydrous ethanol, tetraethyl orthosilicate, boric acid, and deionized water is 8-12:13:1-3:4-6.
Citation Information
Patent Citations
Environment-friendly insulating coating solution used for non-oriented silicon steel and preparation and application thereof
CN102115881A
Preparation method of magnesium alloy surface super-hydrophobic high-temperature-resistant composite film
CN117604510A